2021
DOI: 10.1016/j.vaccine.2021.09.043
|View full text |Cite
|
Sign up to set email alerts
|

Early exploration of COVID-19 vaccination safety and effectiveness during pregnancy: interim descriptive data from a prospective observational study

Abstract: Objective During December 2020, a massive vaccination program was introduced in our country. The Pfizer-BioNTech, BNT162b2 vaccine was first offered exclusively to high-risk population, such as medical personnel (including pregnant women). In this study we compare short term outcomes in vaccinated vs. non-vaccinated pregnant women. Methods In this prospective observational cohort study, vaccinated and non-vaccinated pregnant women were recruited using an online Google f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
62
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(66 citation statements)
references
References 10 publications
3
62
0
Order By: Relevance
“…Three observational studies 22 – 24 examined the effectiveness of mRNA vaccination against SARS-CoV-2 infection, comparing 18,828 vaccinated pregnant people and 18,828 unvaccinated pregnancy controls. While other studies reported on SARS-CoV-2 infection 20 , 30 as an outcome measure, the duration of follow-up and accounting strategy of time-varying confounding were unclear, so they were not included in the quantitative summary.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three observational studies 22 – 24 examined the effectiveness of mRNA vaccination against SARS-CoV-2 infection, comparing 18,828 vaccinated pregnant people and 18,828 unvaccinated pregnancy controls. While other studies reported on SARS-CoV-2 infection 20 , 30 as an outcome measure, the duration of follow-up and accounting strategy of time-varying confounding were unclear, so they were not included in the quantitative summary.…”
Section: Resultsmentioning
confidence: 99%
“…Of 18 observational studies of the impact of COVID-19 vaccination (vs. no vaccination) on pregnancy outcomes, the vast majority were of mRNA vaccines, with very few of viral vector vaccines 8 , 21 , 26 30 , 33 . Twelve studies were observational 8 , 19 , 20 , 22 – 24 , 27 , 29 32 , 34 and three were governmental reports 21 , 28 , 33 . We did not include two studies reporting vaccination side-effects 13 , 26 and a single study 25 reporting antibody levels, as there was no pregnancy control group.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A flowchart of study selection process is reported in Figure 2 . We considered 46 records: 30 of them included pregnant mothers [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ], two studies included both pregnant and lactating mothers [ 39 , 40 ], and 14 studies included lactating mothers [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. Most studies were conducted in the United States (41.3%) and Israel (26.1%), along with three in Italy (6.5%), two in Spain (4.3%) and in Poland (4.3%), and the remaining (17.2%) in the United Kingdom, Qatar, Belgium, Germany, Norway, Portugal, the Netherlands, and Singapore.…”
Section: Resultsmentioning
confidence: 99%